Anomalies in the Expression Profile of Interspecific Hybrids of Drosophila melanogaster and Drosophila simulans - Ranz, José M.; Namgyal, Kalsang; Gibson, Greg; Hartl, Daniel L. (Genome Research, 2004)
When females of Drosophila melanogaster and males of Drosophila simulans are mated, the male progeny are inviable, whereas the female progeny display manifold malformations and are sterile. These abnormalities result from genetic incompatibilities accumulated since the time the lineages of the species diverged, and may have their origin in aberrant gene transcription. Because compensatory changes within species may obscure differences at the regulatory level in conventional comparisons of the expression profile between species, we have compared the gene-expression profile of hybrid females with those of females of the parental species in order to identify regulatory incompatibilities. In the hybrid females, we find abnormal levels of messenger RNA for a large fraction of the Drosophila transcriptome. These include a gross underexpression of genes preferentially expressed in females, accompanying gonadal atrophy. The hybrid females also show significant overexpression of male-biased genes, which we attribute to incompatibilities in the regulatory mechanisms that normally act to control the expression of these genes in females. The net result of the multiple incompatibilities is that the gene-expression profiles of the parental females are more similar to each other than either is to that of the hybrid.
10.1101/gr.2019804